The Impact of Productive Waqf During the Covid-19 Pandemic : Case Study of Waqf Organizer at Wandanpuro Bululawang - Rudy Catur Rohman Kusmayadi; Ririn Noviyanti (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2021)
Since the Covid-19 outbreak in Indonesia, the community's economy need the assistance in the form of basic necessities or in the form of money because they low of income. The existence of waqf, especially productive waqf, is very important in an effort to help this problem. This study aims to analyze the impact of productive waqf during the covid-19 pandemic on community economic resilience at Pengelola Wakaf Desa Wandanpuro Bululawang. This study is qualitatif, using interview and documentation in the data colletion technique. The data collected, analysed by qualitatif method. The results found that waqf, especially productive waqf, is very important in an effort to help the community's economy both to help relieve the main burden of the poor and orphans, either in the form of assistance in the form of basic necessities or in the form of money